1984
DOI: 10.1126/science.6719117
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Metabolites From the Bioactivation of Toxic Methylfurans

Abstract: An important mechanism of toxicity of furans involves the cytochrome P-450 monooxygenase-catalyzed bioactivation of the compound in situ directly within the target tissues to highly reactive electrophilic products. The unsaturated aldehydes acetylacrolein and methylbutenedial have been identified as the principal reactive intermediates of 2- and 3-methylfuran, respectively, that are produced and bound covalently to tissue macromolecules in hepatic and pulmonary microsomal systems in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
93
1
6

Year Published

1990
1990
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 12 publications
2
93
1
6
Order By: Relevance
“…The methyl analogs of furan are metabolically activated in a similar fashion as the parent furan, yielding highly reactive, unsaturated dialdehydes (Ravindranath, Burka, and Boyd 1984;Ravindranath and Boyd 1985). Estimates of dietary exposure have been calculated by conducting surveys of furan levels within foods found in Canada .…”
Section: Introductionmentioning
confidence: 99%
“…The methyl analogs of furan are metabolically activated in a similar fashion as the parent furan, yielding highly reactive, unsaturated dialdehydes (Ravindranath, Burka, and Boyd 1984;Ravindranath and Boyd 1985). Estimates of dietary exposure have been calculated by conducting surveys of furan levels within foods found in Canada .…”
Section: Introductionmentioning
confidence: 99%
“…They are frequently observed in the exhaust plumes and nearby environment of combustion sources. Many studies have shown that they are toxic, whether ingested or inhaled, and thus pose a considerable threat to human health (1)(2)(3)(4). The simplest of these compounds (i.e., unsubstituted furan, C 4 H 4 O) is a cyclic, dienic ether with a low molecular weight, high volatility, and high lipophilicity.…”
mentioning
confidence: 99%
“…Autoradiography revealed that the covalently bound radioactivity was predominantly associated with Clara cells, and in vitro studies suggested that a cytochrome P-450-dependent monooxygenase was required to activate 4-ipomeanol to a reactive metabolite(s) that bound covalently to macromolecules. While much of the early data suggested that the reactive metabolite of 4-ipomeanol was the furan epoxide, studies with 2-and 3-methylfuran identified the unsaturated aldehydes acetylacrolein and methylbutenedial, respectively, as the principal reactive metabolites (62). Thus, in the absence of further data we cannot yet conclude the nature of the reactive metabolites of 4-ipomeanol.…”
Section: -Lpomeanolmentioning
confidence: 88%